World of Warcraft Gold Strategy Guide. - Dekker, Eric (Packt Publishing, 2013)
Rich with examples, detailed breakdowns, and step-by-step instructions, this book gets down to the nuts and bolts of gold making, to help you become a World of Warcraft gold tycoon. This book is for every World of Warcraft player who's tired of scrapping for gold or has ever wanted to be the one showing off expensive items in town.